2004
DOI: 10.1111/j.0004-8461.2004.01310.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of 99mTc‐glucoheptonic acid brain single photon emission computed tomography in differentiation of recurrent brain tumour and post‐radiation gliosis

Abstract: Blood-brain barrier imaging of brain tumours is fast attracting interest now that it has been demonstrated that disruption of the blood-brain barrier is essential for uptake of all tumour-seeking agents. The aim of the present study was to differentiate recurrent tumour from post-radiation gliosis using (99m)technetium-glucoheptonate ((99m)Tc-GHA) as a tumour-seeking agent. Brain single photon emission computed tomography (SPECT) with (99m)Tc-GHA was performed in 73 patients with primary malignant brain tumour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…[36][37][38] The use of 99m technetium ( 99m Tc)-glucoheptonic acid and 123 iodine-( 123 I) alpha-methyl-tyrosine had similar accuracy (93% and 96%) in detecting recurrence. 39 Another tracer, 99m Tchexakis-2-methoxyisobutylisonitrile, is reported to provide better sensitivity (93% and 89%) than specificity (83% and 83%) for identifying recurrence. 40,41 Thallium is superior to other tracers because there is no tracer uptake in a healthy brain.…”
Section: Spectmentioning
confidence: 99%
“…[36][37][38] The use of 99m technetium ( 99m Tc)-glucoheptonic acid and 123 iodine-( 123 I) alpha-methyl-tyrosine had similar accuracy (93% and 96%) in detecting recurrence. 39 Another tracer, 99m Tchexakis-2-methoxyisobutylisonitrile, is reported to provide better sensitivity (93% and 89%) than specificity (83% and 83%) for identifying recurrence. 40,41 Thallium is superior to other tracers because there is no tracer uptake in a healthy brain.…”
Section: Spectmentioning
confidence: 99%
“…It's often difficult to distinguish radiation necrosis and tumor recurrence. They could have the same clinical and imaging aspects but the distinction between these two causes of neurological deterioration is crucial for the subsequent therapeutic decision-making (2,4,12). In the present study MRS was successful in distinguishing radiation necrosis and recurrence of tumor.…”
Section: Discussionmentioning
confidence: 52%
“…Of the 26 articles deemed eligible for inclusion [9][10][11], two pairs of articles (Schwartz et al [21] and Carvalho et al [22], and Barai et al [31] and Barai et al [33]) had overlapping data; thus, only the articles with the most data, that is, those of Carvalho et al [22] and Barai et al [33], were included.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…Analysis of radiotracers showed that thallium-201 ( 201 Tl) was the most frequently used tracer in 12 studies [ Tc-glucoheptonate ( 99m Tc-GH) [9,33,35]. Four studies compared different SPECT radiotracers, 201 Tl versus 99m Tc hexamethylpropylene amine oxime ( 99m Tc-HMPAO) [22], 99m Tc-MIBI versus 201 Tl [30], 99m Tc-MIBI versus 123 I-IMT [29], and 99m Tc-GH versus 201 Tl [35].…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%